Nulidade parcial sem redução de texto: um mecanismo constitucionalizante e seu modo de ser a partir da hermenêutica filosófica - Mello, Rafael Corte (Universidade do Vale do Rio do Sinos, 2006)
The central object is to show to the relation between the Brazilian legal tradition and the paradigm of modernity forged for the Metaphysical philosophy as being obstacles to the reach of the concretion of the rights. Although critical to modernity and the formal repudiation to the positivism already to have reached the common place of the academic activities, the daily one of the jurist shows the opposite. A linked hermeneutic boarding with important parcel of the historical and philosophical structure of the legal tradition is used to display such circumstances. The scope of the civil action will be detached in the search for the identification of this tradition for being the area of the Law that more was dedicated to the studies of the jurisdictional activity. In this this sense, the constitutional adjudication is presented with the ideal place for the identification of negative preconceptions that if for had surpassed. The intent control of constitutionality exerted by means of the Teilnichtigerklärung oh
Keywords: controle de constitucionalidade; hermenêutica; hermenêutica filosófica; jurisdição; nulidade parcial; tradição jurídica; constituição; Ciências Sociais Aplicadas